Status epilepticus in pregnancy: a literature review and a protocol proposal. (3rd April 2022) - Roberti, Roberta; Rocca, Morena; Iannone, Luigi Francesco; Gasparini, Sara; Pascarella, Angelo; Neri, Sabrina; Cianci, Vittoria; Bilo, Leonilda; Russo, Emilio; Quaresima, Paola; Aguglia, Umberto; Di Carlo, Costantino; et al.
ABSTRACT: Introduction: Status epilepticus (SE) in pregnancy represents a life-threatening medical emergency for both mother and fetus. Pregnancy-related pharmacokinetic modifications and the risks for fetus associated with the use of antiseizure medications (ASMs) and anesthetic drugs complicate SE management. No standardized treatment protocol for SE in pregnancy is available to date. Areas covered: In this review, we provide an overview of the current literature on the management of SE in pregnancy and we propose a multidisciplinary-based protocol approach. Expert opinion: Literature data are scarce (mainly anecdotal case reports or small case series). Prompt treatment of SE during pregnancy is paramount and a multidisciplinary team is needed. Benzodiazepines are the drugs of choice for SE in pregnancy. Levetiracetam and phenytoin represent the most suitable second-line agents. Valproic acid should be administered only if other ASMs failed and preferably avoided in the first trimester of pregnancy. For refractory SE, anesthetic drugs are needed, with propofol and midazolam as preferred drugs. Magnesium sulfate is the first-line treatment for SE in eclampsia. Termination of pregnancy, via delivery or abortion, is recommended in case of failure of general anesthetics. Further studies are needed to identify the safest and most effective treatment protocol.